2009
DOI: 10.1158/0008-5472.can-08-2478
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Signatures of a Subset of High-Grade Premalignant Cervical Lesions Closely Resemble Invasive Carcinomas

Abstract: Cervical cancer develops from precancerous high-grade cervical intraepithelial neoplasia (CIN) harboring a transforming infection with high-risk human papillomavirus, which is characterized by p16INK4a overexpression. Once such a lesion has developed, progression toward an invasive squamous cell carcinoma (SCC) may take one or more decades, underlining the heterogeneity of these lesions in terms of duration of existence and progression risk. We performed array-based comparative genomic hybridization (array CGH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 55 publications
6
46
0
1
Order By: Relevance
“…For end-point measure CIN2 þ cytology and the combination of cytology and HPV 16/18 genotyping performed slightly better than the methylation panel. Possible reasons for low methylation levels in these cases could be sampling error, the presence of early onset CIN3 lesions with few chromosomal abnormalities (38), or CIN2 lesions representing productive hrHPV infections with a low risk to progress to invasive cancer till the next screening round after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…For end-point measure CIN2 þ cytology and the combination of cytology and HPV 16/18 genotyping performed slightly better than the methylation panel. Possible reasons for low methylation levels in these cases could be sampling error, the presence of early onset CIN3 lesions with few chromosomal abnormalities (38), or CIN2 lesions representing productive hrHPV infections with a low risk to progress to invasive cancer till the next screening round after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…25 --28 In cervical cancer we previously showed that particularly gains on chromosomes 1, 3q and 20q may be involved in malignant progression. 29 Integration of chromosomal alterations with miRNA expression may further clarify the functional role of frequent chromosomal alterations and aid in the identification of novel potential tumour suppressors and oncogenes in cervical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide miRNA expression profiles of micro-dissected specimens of normal squamous epithelium, CIN2 --3, SCCs and AdCAs were obtained and directly integrated with previously generated chromosomal profiles of the same samples. 29,30 Functional effects of altered expression of hsa-miR-9, which was associated with a frequent chromosomal gain, were further investigated in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that the genotypes detected could be influenced by allelic somatic losses in the dysplastic cervical epithelium seems rather unlikely. First, cytologic specimens used in this study comprised cells from the whole uterine cervix, including both dysplastic and normal cells, and second, comparative genomic hybridization experiments have demonstrated that the entire or fragments of chromosome 1, where the FcGR3A locus is present, have not been found to be affected by loses in SIL or CC [30]. FcGR3A gene is not subjected to genetic rearrangements as those happening in IgH and TCR genes during B-and T-cell lymphocyte maturation, respectively.…”
Section: Discussionmentioning
confidence: 99%